2007
DOI: 10.1002/jcc.20575
|View full text |Cite
|
Sign up to set email alerts
|

Improved grid‐based algorithm for Bader charge allocation

Abstract: An improvement to the grid-based algorithm of Henkelman et al. for the calculation of Bader volumes is suggested, which more accurately calculates atomic properties as predicted by the theory of Atoms in Molecules. The CPU time required by the improved algorithm to perform the Bader analysis scales linearly with the number of interatomic surfaces in the system. The new algorithm corrects systematic deviations from the true Bader surface, calculated by the original method and also does not require explicit repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
2,260
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 3,569 publications
(2,314 citation statements)
references
References 16 publications
52
2,260
0
2
Order By: Relevance
“…(3)] are consistent with those obtained by the conventional volume integration methods. The differences do not exceed 0.11 e between the charges from BADERWIN (Sanville et al, 2007) and those from the flux of the electric field. However, discrepancies are larger between the charges obtained from NEWPROP (Souhassou, 1999;Souhassou & Blessing, 1999) and those of the two other methods, and even reach 0.35 e for the C9 atom.…”
Section: Electrostatic Potential and Fieldmentioning
confidence: 78%
See 2 more Smart Citations
“…(3)] are consistent with those obtained by the conventional volume integration methods. The differences do not exceed 0.11 e between the charges from BADERWIN (Sanville et al, 2007) and those from the flux of the electric field. However, discrepancies are larger between the charges obtained from NEWPROP (Souhassou, 1999;Souhassou & Blessing, 1999) and those of the two other methods, and even reach 0.35 e for the C9 atom.…”
Section: Electrostatic Potential and Fieldmentioning
confidence: 78%
“…Recently, an entirely numerical and robust computation to define the atomic basins and to integrate the electrons to obtain AIM charges was developed by Henkelman et al (2006) and is based on the steepest ascent algorithm (Sanville et al, 2007). This approach has been implemented in the BADERWIN program (Sanville et al, 2007).…”
Section: Topological Analyses and Derived Atomic Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge distributions of Sr and O surface atoms for 3 and 6 unit cell thickness of thin film were compared by using Bader code. [62][63][64] It was found that strontium and oxygen ions bear 1.54 e and -1.37e charges, respectively, for 3 unit cell and 1.54 e and -1.27 e charges, respectively, for 6 unit cell thicknesses. One can see some small difference for the atomic charge of O ions, while the charge state of Sr ions remains intact.…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…Bader charge analysis 26 was used to estimate charge transfer using the Henkelmans group program. [27][28][29] Our calculated macroscopic dielectric constants using the Kohn-Sham independent-particle picture were collected by using a (11 Â 11 Â 5) grid for stage 1 and (7 Â 7 Â 5) for stage 2.…”
Section: Computational Detailsmentioning
confidence: 99%